Aspek Hukum Penggunaan Surat Berharga Pada Dunia Perbankan Bagi Masyarakat Indonesia - Roziana , Refsi; Efendi , Fithria Habib; Herlika, Eren; Ameilia, Deva; Utami, Aisyah Putri (Universitas Dehasen Bengkulu, 2024)
Indonesia's economic activities, Indonesia's economic development is inseparable from the role of the banking world, which is the main driving force for the national economy. The world of banking acts as an intermediary for the real sector and the financial sector in people's economic activities. In its activities, banking collects and distributes funds from the public and then returns them to the community in the form of credit or money loans. Indeed, in the context of banking life, both customers depositing funds and customers receiving funds are equally important. Because it is from both sides of the customer that the bank can run its business. From customers depositing bank funds, they will receive business capital, which then from customers receiving funds, the funds are channeled by obtaining profits in the form of interest. It can be said that the bank's business is to take advantage of the difference between the interest on savings/deposits, and the interest on the loans it distributes. Thus it can be said that the existence of customers is the